Effectiveness assessment of using water environmental microHI to predict the health status of wild fish - Yang, Haile; Zhong, Jia; Leng, Xiaoqian; Wu, Jinming; Cheng, Peilin; Shen, Li; Wu, Jinping; Li, Pengcheng; Du, Hao (Frontiers in Microbiology, 2024)
Aquatic wildlife health assessment is critically important for aquatic wildlife conservation.However, health assessment of aquatic wildlife (especially aquatic wild animal) is difficult, and often accompanied by biological destruction and delayed observability. As there is growing evidence that aquatic environmental microbiota could impact the health status of aquatic animals through influencing the symbiotic microbiota, we proposed a non-invasive method for monitoring health status of aquatic wild animals using environmental microbiota health index (microHI). However, it's unknown whether this method is effective in different ecotype groups of the aquatic wild animals. To answer this question, we took a case study in middle Yangtze River and studied the water environmental microbiota and fish gut microbiota at fish community level, population level and ecotype level. The results showed that the gut microHI of healthy group was higher than that of unhealthy group at community level and population level, and the overall gut microHI was positively correlated with water environmental microHI, whereas the gut microHI baseline was species-specific. Integrating these variations, in 4 ecotype groups (filter-feeding, scraper-feeding, omnivorous, carnivorous), only the gut microHI of carnivorous group positively correlated with water environmental microHI. Alcaligenaceae, Enterobacteriaceae and Achromobacter were the most abundant groups with health-negative-impacting phenotypes, had high positive correlations between gut sample group and environment sample group and significantly higher abundance in unhealthy groups than in health groups of carnivorous, filter-feeding and scraper-feeding ecotypes. Therefore, using water environmental microHI to indicate the health status of wild fish is effective at community level, as well as carnivorous fish at ecotype level. In middle Yangtze River, Alcaligenaceae, Enterobacteriaceae (family level) and Achromobacter (genus level) were the key water environmental microbial groups that potentially impacted wild fish health status. Of course, more data and researches that test the current hypothesis and conclusion are encouraged.